The Helsinki Declaration on Patient Safety in Anesthesia – Russian Experience: a Questionnaire Survey - T. A. Kabanova; P. A. Degtyarev; M. I. Shkerdina; A. P. Kostikov; M. Ya. Khalimov; E. V. Tereschenko; M. A. Babaev (Вестник анестезиологии и реаниматологии)
The objective: to determine the quality of knowledges about the Helsinki Declaration on Patient Safety among Russian anesthesiologists and intensivists and how widely its vision and standards have been adopted in clinical practice.Subjects and Methods. The study design involved the creation of 44-item online and offline questionnaire. The questions were divided into three blocks: personal information, data on hospitals where respondents work, and questions about implementation of the Helsinki protocol in their practice. Some of the questions required open answers. Persons with higher medical education who have completed residency and/or internship in anesthesiology and resuscitation and are working in this field in the Russian Federation were invited to participate in the survey.Results. 140 (21.5%) respondents answered all the question of the questionnaire. Of those surveyed, 76.4% were familiar with the Helsinki Declaration on Patient Safety, but only 17.1% felt they had sufficient knowledge of the concept. 43.6% of the respondents apply the Helsinki Declaration on Patient Safety to their clinical practice, while 49.3% of the respondents had difficulty answering whether they follow the Declaration in their work or not. The study showed a satisfactory level of compliance with mandatory standards for monitoring in the perioperative period but all the EBA-recommended standards are applied in only 23% of the hospitals. 26.4% of the respondents use the Safe Surgery Checklist prepared by the World Health Organization. 58.6% of the respondents use the reporting/notification system for adverse events or critical conditions in the perioperative period.Conclusion. The survey has shown that many of the surveyed anesthesiologists and intensivists have good knowledge of the Helsinki Declaration on Patient Safety and successfully apply it to their clinical practice but some doctors do it unconsciously, not understanding what standards they follow. Organization of additional educational programs could help physicians to improve their knowledge and raise their awareness in order to provide safer patient care. We also suggest introduction of unified checklists and national reporting systems for adverse events or critical conditions in the perioperative period.